Effects of supplementing tributyrin on serum biochemical indices and meat quality characteristics of longissimus thoracis et lumborum of weaned Small-Tailed Han lambs - Ya-Xin Wang; Xue-Er Wang; Zhi-Wei Li; Ran An; Qing-Chang Ren; Jian-Zhuang Tan (Animal Nutriomics)
This experiment aimed to investigate the impacts of tributyrin (TB) dietary supplementation on serum biochemical indices and meat quality characteristics of longissimus thoracis et lumborum (LTL) muscle of lambs after weaning. Thirty healthy Small-Tailed Han female lambs (27.5 ± 4.1 kg; mean ± standard deviation) were randomly assigned to five treatments: basal diet (1) without TB, (2) with 0.5 g/kg TB, (3) with 1.0 g/kg TB, (4) with 2.0 g/kg TB or (5) with 4.0 g/kg TB. Each treatment consisted of six lambs, and the lambs were weaned on d 90 and were raised until d 165. Results showed that supplementing TB significantly promoted serum immunoglobulin concentrations of lambs such as immunoglobulins G, A and M. Besides, TB significantly increased muscle ether extract content, intermuscular fat length, pH value and redness but decreased lightness, drip loss and shear force. In addition, TB significantly elevated inosine-5ʹ-phosphate content and upregulated the relative expressions of genes related to lipid metabolism such as SREBP-1C, SCD, PPARγ, FAS and LPL. The mostly important, TB significantly enhanced essential amino acids (EAAs) and conjugated linoleic acids contents of the LTL muscle, despite it decreased total unsaturated fatty acids level. In conclusion, supplementing TB not only could promote the healthy status of weaned lambs via promoting serum immunity but also may improve nutritional quality of LTL muscle by improving EAA and conjugated linoleic acid contents.